Transcriptomic analysis reveals the regulatory mechanism of tetraspore formation in Gracilariopsis lemaneiformis - Sun, Deguang; Zhou, Xueyou; Sun, Xue; Xu, Nianjun (Frontiers in Marine Science, 2023)
With the expansion of seaweed culture and changes in the global climate, large quantities of new seaweed germplasm are urgently needed. It is important to elucidate the process of reproductive development and its regulatory mechanism in seaweed. Gracilariopsis lemaneiformis (Rhodophyta) has an essential economic and ecological value, for example, as a raw material for agar extraction and abalone feed. Here, four phases (I to IV) of G. lemaneiformis tetrasporophyte development were analyzed using physiological assays and transcriptome technologies. The results showed that photosynthetic capacity increased during the period from tetraspore formation to the release (Phase II, III and IV). According to transcriptome results, the expression levels of genes associated with light harvesting, photosynthesis, and carbon fixation pathways were significantly upregulated during tetraspore formation and release. Meanwhile, the expression levels of genes encoding starch and trehalose synthesis enzymes in starch and sucrose metabolism were enhanced during tetraspore formation and release, suggesting that G. lemaneiformis requires more energy supply during reproductive development, and that trehalose-6-phosphate may also act as a signaling molecule to induce tetraspore formation. In addition, genes encoding antioxidant enzymes (APX, TRX, GR, TR, PRX, and CAT) were significantly upregulated during tetraspore formation. These results may help us to understand the transition from nutritional to reproductive development and the molecular mechanism of G. lemaneiformis tetrasporogenesis, which is vital for the development of new germplasm and promoting the growth of the seaweed culture industry.